Misinformation, infighting, backlash, and an 'endless' recovery; policymakers recount challenges and mitigating measures after a vaccine scare in the Philippines. Issue 1 (31st December 2022) - Reñosa, Mark Donald C.; Wachinger, Jonas; Bärnighausen, Kate; Endoma, Vivienne; Landicho-Guevarra, Jhoys; Landicho, Jeniffer; Bravo, Thea Andrea; Aligato, Mila; McMahon, Shannon A.
ABSTRACT: Background: Vaccine scares undermine longstanding global health achievements. Remarkably little data has documented the lived experiences of policymakers working amidst vaccine scares and navigating their fallout. As a result, chances and challenges of large-scale national recuperation efforts are poorly understood. Objective: This study aims to explore the perspectives of policymakers involved in ongoing efforts to boost vaccine confidence in the Philippines following a 2017 Dengvaxia scare and the current COVID-19 pandemic. Methods: Between August and November 2020, we conducted 19 semi-structured narrative interviews with purposively selected policymakers from governmental agencies and non-governmental organizations in the Philippines. Interviews were conducted online, transcribed, and analyzed following the tenets of reflexive thematic analysis. Results: We present results as an emerging model that draws on a chronology conveyed by policymakers in their own words. The Dengvaxia scare proved 'a decisive wedge' that splintered Filipino society and pitted governmental agencies against one another. The scare stoked distorted vaccination narratives, which were 'accelerated rapidly' via social media, and ignited feelings of uncertainty among policymakers of how to convey clear, accurate health messaging and how to prevent drops in care-seeking more broadly. Conclusions: Efforts to regain trust placed exceptional burdens on an already-strained health system. Respondent-driven recommendations on how to reinforce vaccine confidence and improve vaccination rollout include: developing clear vaccine messages, fostering healthcare providers' and policymakers' communication skills, and rebuilding trust within, toward and across governmental agencies. Further research on how to build enabling environments and rebuild trust in and across institutions remains paramount.